IMPLEMENTASI KEWAJIBAN PENGGUNAAN LABEL BERBAHASA INDONESIA PADA BARANG YANG DIPERDAGANGKAN DI DALAM NEGERI (STUDI KASUS DI KOTA SINGARAJA) - Vivi Sandra; ardhya, si ngurah; landrawan, i wayan (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze and examine the implementation of the obligation to use Indonesian language labels on goods traded domestically as regulated in Article 8 paragraph (1) letter j UUPK Jo Article 20 paragraph (1) PP Number 29 of 2021 concerning the Implementation of the Trade Sector Jo Article 97 paragraph (3) of Law Number 18 of 2012 concerning Food and the legal consequences for business actors who do not include Indonesian language labels on goods traded domestically in Singaraja City. The type of research used is descriptive empirical juridical research. The sample used was purposive sampling. Data collection techniques include document study, observation and interviews. Data processing and analysis was carried out qualitatively. Based on the research conducted, it is known that the implementation of the obligation to use Indonesian language labels on goods traded in Singaraja City has not been implemented well by food product business actors. The legal consequences for business actors who violate are subject to sanctions as stated in Article 62 paragraph (1) UUPK in conjunction with Article 26 paragraph (1) PP Number 29 of 2021 concerning the Implementation of the Trade Sector.